Development of the 2D mobile game “Highwash Rush” with the theme of avoiding vehicle obstacles using unity with the MDCL method - Aju, Charmiyanti Nurkentjana; Yasir, Yusran; Falaq, Indah Fajrin Kamil; Wibisono, Dwi (Priviet Social Sciences Journal, 2025)
Among the most prevalent forms of digital entertainment are two-dimensional (2D) mobile games, which are engaging, readily accessible, and compatible with a wide range of devices. This study sought to design and implement a 2D obstacle-avoidance game using Unity. The development methodology employed is the Multimedia Development Life Cycle (MDLC), comprising six stages: concept, design, material collection, assembly, testing, and distribution. The game, named Highwash Rush, was developed with various control features, including gyroscope sensors, swipe gestures, and directional buttons, and is equipped with a progressive scoring system and sound effects to enhance player experience. Black Box and Alpha Testing conducted on several Android devices demonstrated that the game operated stably, responded effectively, and adhered to the original design specifications. The findings suggest that implementing the MDLC method, excluding the distribution stage, in unity-based educational game development is effective for producing engaging and interactive multimedia applications suitable for practical use.